FORMATION OF THE COMMITMENT TO NATIONAL AND HUMAN VALUES IN CHILDREN AND YOUTH IS AN IMPORTANT PRIORITY OF THE ESSENTIAL LAW - Djavakova K (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The article reveals the essence and importance of the formation of commitment among children and youth to national and universal values, analyzes the legal conditions, regulatory legal acts adopted in Uzbekistan and devoted to the effectiveness of youth policy. The article considers the importance of patriotic education, which consolidates society and prevents the worst qualities in people from manifesting themselves - indifference, selfishness, individualism, cynicism, unmotivated aggression, disrespect for the state and its social institutions.